Communication Problems and Problem-Solving Strategies of People with Autism Spectrum Disorder in Fly Away, Jack of the Red Hearts, What’s Eating Gilbert Grape and the Night Clerk (a Psycholinguistics Study) - Titik Sudiatmi; Sri Wahono; Sri Muryati (Jurnal Multidisiplin Madani, 2023)
People with autism do not react and communicate like most people. Communication problems in ASD sufferers are verbal and non-verbal. In achieving the research objectives, the researcher uses a qualitative descriptive method because the data in the form of speech from each character in each film has been analyzed. Based on the analysis that has been done, it is found that 60 data, the most common and dominant communication problem experienced by the characters in the four films is the problem of conversation. Other communication problems found were repetition, lack of sensitivity to social cues and poor understanding of roles. The problem solving strategy found and dominant in the films analyzed is learning. Other problem solving strategies found are skills, rules and assignments. A person with autism learns how they can solve problems to be able to adjust to their social environment